Practices of Corporate Social Responsibility: A Study on some Islamic Organizations in Bangladesh - Haque, Md Shariful; Ahmad, Md Mokhter (IIUC Studies, 2012)
Corporate Social Responsibility (CSR) is a commitment of the organizations to act ethically and contribute to economic development of the society while humanizing the quality of life of the workforce and the local community at large. This is a talented issue for the corporation the world over. CSR is required for the organizations to ensure its sustainability. Now-a-days the practice of CSR is subject to much debate and criticism. Critics argue that CSR deviates from the fundamental economic role of business; others argue that it is nothing more than superficial windowdressing; others yet argue that it is an attempt to pre-empt the role of governments as a watchdog over powerful multinational corporations. Notwithstanding, CSR is a global concern and all organizations practice it to some extent. In this article the authors made an effort to justify CSR and the concomitant issues in the light of Shar?ah, and examine the welfare practices of some Islamic Organizations in Bangladesh to see whether those fall under the traditional concept of CSR. An investigation has been made into some Islamic organizations in Bangladesh using an unstructured questionnaire. It transpires from the study that almost all these investigated Islamic organizations practice social responsibilities in different forms like Qard-EHasanah, scholarships/stipends, plantation, health services, establishing schools etc. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12271 IIUC Studies Vol.7 2011: 249-282